Evaluation and delivery of disease resistant cassava varieties with comparable micronutrient density to farmers in Cameroon - Njukwe, E.; Amah, D.; Ndango, R.; Tindo, M.; Dixon, A.; Tenkouano, A. (International Institute of Tropical Agriculture, 2010)
Cassava (Manihot esculenta Crantz) is one of the most important staple food crops of the people in Cameroon, with some estimated 204,548 hectares devoted to it and corresponding annual production of 1,998,819 metric tons. It plays a major role in efforts to alleviate food crisis due to its efficient production of food energy, year-round availability, tolerance to extreme stress conditions, and suitability to present farming and food systems. Traditionally, cassava roots are processed by various methods into numerous products and utilized in various ways according to local customs and preferences while the leaves are consumed as vegetables. However, traditional varieties have become relative unproductive, due to a combination of biotic and abiotic constraints, thus justifying the necessity to cultivate improved varieties. In recent years, the International Institute of Tropical Agriculture (IITA) has used conventional breeding methods to achieve important breakthrough in developing pest and disease resistant varieties with low cyanide content, short crop cycle, high-yield and micronutrient content. However, these varieties still require further testing, validation and possibly adaptation to local conditions, before farmers will adopt them. Thus from 2001, over 500 new varieties introduced from Nigeria have undergone advanced yield trials at Mbalmayo (3o 25N latitude, 11o 28E longitude and 640masl) resulting in further selection for uniform yield and multilocational trials with significant contribution from farmers. In 2004 ten varieties (BBulk P6, 8085, 880447-2, 880713, 92/0057, 92/0326, 95/0109, 96/0023, 96/1414 and 96/1762) with excellent resistance to pest and diseases, high root yield (>20 tons ha-1), high dry matter content (>35%), high iron content (>5ug/g), high zinc content (>7 ug/g) and high total carotenoid content (>0.7 ug/g) were selected and are being tested in seven provinces of Cameroon. Results indicate good performance of improved varieties. Due to restrictions on across border movement of planting materials resulting from quarantine regulations, availability of sufficient improved varieties to meet farmers’ needs is limited by IITA’s capability to respond to requests. Hence the adoption of evaluation, multiplication and delivery hubs serving as focal points to satellite centers that will provide planting material of improved varieties to farmers. Adoption of these varieties in Cameroon may make significant contribution to food security and poverty alleviation.